2009
DOI: 10.1111/j.1757-5672.2009.00005.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Blood Pressure and Nocturia in Hypertensive Patients

Abstract: Objective: We investigated the relationship between the pattern of hypertension and nocturia. Methods: Seventy-seven patients who were being treated for hypertension completed a questionnaire regarding the number of times they urinated during the day and at night, and measured their blood pressure at home immediately after rising in the morning and just before going to sleep at night. The patients' blood pressure was also measured at the clinic. The patients were divided into groups according to their blood pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In our previous studies, nighttime plasma catecholamine levels and daytime blood pressure were higher in healthy elderly persons with nocturia who were not on any medications than in healthy elderly persons without nocturia and medications, and nocturnal frequency was higher in BPH patients with untreated hypertension than in BPH patients without hypertension . Among hypertensive patients, daytime urination is less frequent in patients with sustained hypertension than in those who are normotensive with treatment or those with white coat hypertension, while nighttime urination is more frequent in hypertensive patients with a morning surge (morning systolic blood pressure ≥15 mmHg higher than at night) . Therefore, although there is a relationship between the frequency of urination and blood pressure or indicators of sympathetic activity such as plasma catecholamine levels, high blood pressure or high plasma catecholamine levels do not necessarily lead to nocturia.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In our previous studies, nighttime plasma catecholamine levels and daytime blood pressure were higher in healthy elderly persons with nocturia who were not on any medications than in healthy elderly persons without nocturia and medications, and nocturnal frequency was higher in BPH patients with untreated hypertension than in BPH patients without hypertension . Among hypertensive patients, daytime urination is less frequent in patients with sustained hypertension than in those who are normotensive with treatment or those with white coat hypertension, while nighttime urination is more frequent in hypertensive patients with a morning surge (morning systolic blood pressure ≥15 mmHg higher than at night) . Therefore, although there is a relationship between the frequency of urination and blood pressure or indicators of sympathetic activity such as plasma catecholamine levels, high blood pressure or high plasma catecholamine levels do not necessarily lead to nocturia.…”
Section: Discussionmentioning
confidence: 88%
“…17 Among hypertensive patients, daytime urination is less frequent in patients with sustained hypertension than in those who are normotensive with treatment or those with white coat hypertension, while nighttime urination is more frequent in hypertensive patients with a morning surge (morning systolic blood pressure ≥15 mmHg higher than at night). 18 Therefore, although there is a relationship between the frequency of urination and blood pressure or indicators of sympathetic activity such as plasma catecholamine levels, high blood pressure or high plasma catecholamine levels do not necessarily lead to nocturia.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed a significant relationship between hypertension and bothersome nocturia. Uncontrolled hypertension and elevation of blood pressure are reportedly related to nocturia 9,37 . Hypertension affects renal glomerular filtration and tubular transport.…”
Section: Discussionmentioning
confidence: 99%